PENDIDIKAN ANTI KORUPSI DALAM PERSPEKTIF BUDAYA MELAYU - Budiman, Amat (Jurnal Pendidikan Guru, 2017)
Â Anti-corruption education is a cultural process to make human life better and more meaningful with conscious and planned effort to realize the teaching and learning process which is critical to anti corruption value. In the perspective of Malay culture, the values of anti-corruption education are derived from the guidance or purpose of Malay peoples life, namely the Tunjuk Ajar Melayu from pantun, ungkapan, Gurindam Twelve and others. All Malay cultural values can be promoted to prevent and reduce corruption in society and government.Â